Delayed lupus nephritis in the course of systemic lupus erythematosus is associated with a poorer treatment response: a multicentre, retrospective cohort study in Japan. (August 2019) - Nakano, M; Kubo, K; Shirota, Y; Iwasaki, Y; Takahashi, Y; Igari, T; Inaba, Y; Takeshima, Y; Tateishi, S; Yamashita, H; Miyazaki, M; Sato, H; et al.
Objective: The objective of this study was to investigate possible differences in treatment responses between two categories for the onset of lupus nephritis. Methods: We performed a multicentre, retrospective cohort study of class III–V lupus nephritis patients diagnosed between 1997 and 2014. The renal responses to initial induction therapy were compared between patients who developed lupus nephritis within one year from diagnosis of systemic lupus erythematosus (early (E-) LN) and the remainder (delayed (D-) LN) using the Kaplan–Meier method. We determined the predictors of renal response as well as renal flares and long-term renal outcomes using multivariate Cox regression analyses. Results: A total of 107 E-LN and 70 D-LN patients were followed up for a median of 10.2 years. Log-rank tests showed a lower cumulative incidence of complete response in D-LN compared with E-LN patients. Multivariate analysis identified D-LN (hazard ratio (HR) 0.48, 95% confidence interval (CI) 0.33–0.70), nephrotic syndrome at baseline, and a chronicity index greater than 2 as negative predictors of complete response. D-LN patients were more likely to experience renal flares. D-LN (HR 2.54, 95% CI 1.10–5.83) and decreased renal function were significant predictors of chronic kidney disease at baseline. Conclusion: D-LN was a predictor of poorer treatment outcomes, in addition to renal histology and severity of nephritis at lupus nephritis onset.